2016
DOI: 10.2106/jbjs.15.01495
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Cellular Therapy for Osteoarthritis and Focal Cartilage Defects of the Knee

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 50 publications
0
83
0
3
Order By: Relevance
“…Others have postulated that the beneficial effects of BMAC are related to the mesenchymal stem cell (MSC) content. 7 The number of MSCs in BMAC, although relatively small in quantity, varies depending on the site of harvest and patient sex and age. 13 Lavasani et al postulated that the therapeutic effects of MSCs were mediated by secreted factors.…”
Section: Application Of Bmacmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have postulated that the beneficial effects of BMAC are related to the mesenchymal stem cell (MSC) content. 7 The number of MSCs in BMAC, although relatively small in quantity, varies depending on the site of harvest and patient sex and age. 13 Lavasani et al postulated that the therapeutic effects of MSCs were mediated by secreted factors.…”
Section: Application Of Bmacmentioning
confidence: 99%
“…[1][2][3][4] After density gradient centrifugation to remove red blood cells, granulocytes, immature myeloid precursors, and platelets, progenitor cells account for a small population within the bone marrow (0.001% to 0.01%). [5][6][7] However, a high concentration of growth factors, including platelet-derived growth factor, transforming growth factor-b, and bone morphogenetic proteins 2 and 7, which are reported to have anabolic and antiinflammatory effects, [8][9][10] are present in BMAC. Of note, it has been reported that BMAC has a considerable concentration of interleukin-1 receptor antagonist (IL-1RA).…”
mentioning
confidence: 99%
“…These histological observations suggest that inflammation subsides under this pathology [39]. PRP releases growth factors and cytokines that reduce inflammation, and stimulate cartilage regeneration [41]. Ozone could act on inflammation, modulate it and act on many other targets such as growth factors, stem cells, inflammatory cytokines, all of them could stimulate chondrocyte growth and cartilage repair [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the body of literature is highly heterogeneous (with regard to indications, processing method, number, and form of applications), the improvements reported are usually modest and randomized, and unblinded methodologies do not control for patient‐ or clinician‐related bias. As a result, no strong conclusions can be drawn, suggesting that current methods of cell therapy provide generalizable benefits to patients …”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…As a result, no strong conclusions can be drawn, suggesting that current methods of cell therapy provide generalizable benefits to patients. 212 Tissue-engineered scaffolds, synthetics, nanotechnologies, bioprinting, and rapid-prototyping are alternative favorable approaches. However, it is equally difficult to remodel cartilage and bone tissues with implantable scaffolds, synthetics, and nanomolecules, because physical ailments and biomechanical derangements caused by injury, trauma, or wear and tear can impair their function.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%